ANALISIS SISTEM PENDIDIKAN NEGARA FEDERASI RUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN INDONESIA - Irwan Fathurrochman; Sudarwan Danim; Syaiful Anwar AB; Nina Kurniah; Connie Connie; Wachidi Wachidi; Dina Hajja Ristianti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2021)
This study described the education system of the Russian Federation and its implementation in the education system in Indonesia. The results of the study show that there are many differences in the education system. The structure of the basic education curriculum in the Russian Federation has more hours per week than in Indonesia, but in one year the study time in Russia is shorter than in Indonesia. The assessment system for learning outcomes in Russia and Indonesia has something in common, namely that it functions as a basis of information to determine the competencies that have been obtained by students, not as a measure for classifying students into groups. Indonesia has better education management, which is able to manage all educational resources by several people in one education system to achieve educational goals both macro and micro. The State of the Russian Federation views that the management of education is an important matter in the management of educational institutions. The Indonesian state manages issues in education management in general into four main focuses of education management, namely the quality of education, expansion and equity of quality education services, relevance, effectiveness and efficiency.